Assessment and optimization of the fast inertial relaxation engine (fire) for energy minimization in atomistic simulations and its implementation in lammps - Guénolé, Julien; Nöhring, Wolfram G.; Vaid, Aviral; Houllé, Frédéric; Xie, Zhuocheng; Prakash, Aruna; Bitzek, Erik (Computational materials science, 2020)
•An improved version of the FIRE algorithm is now implemented in LAMMPS.•The widely used FIRE algorithm requires a symplectic time integration scheme.•Default parameters are recommended to ensure optimal performance.•Its application is shown and discussed using multiple examples from materials science. In atomistic simulations, pseudo-dynamical relaxation schemes often exhibit better performance and accuracy in finding local minima than line-search-based descent algorithms like steepest descent or conjugate gradient. Here, an improved version of the fast inertial relaxation engine (fire ) and its implementation within the open-source atomistic simulation code lammps is presented. It is shown that the correct choice of time integration scheme and minimization parameters is crucial for the performance of fire.